Access to community forest benefits: Need driven or interest driven? - Ajay Karki; Bishnu Hari Poudyal (Research in Globalization, 2021)
The poverty reduction, livelihood improvement, and equity promotion potential of Community Forests (CF) from a theoretical point of view are indisputable, but their realization appears more questionable because of the setting and enforcement of rules which limit the access to CFs and forest products. This manuscript is prepared based on the data from 45 CF User Groups (CFUGs) including 1111 households of Nepal. This paper aims to determine the level of access to different forest products (firewood, fodder, timber), redistribution of natural resource value (loan), and CFUG-funded public infrastructure (irrigation, electricity, schooling, water) among different groups of users based on social (caste), political (executive committee membership, political elite), and socioeconomic categories (wellbeing ranks). Pair-wise test was done to understand, if there is any significant difference in access to benefits between these groups. Logistic regression was run to know the relationship of different independent variables with access to forest products and forest-accrued benefits. Statistical analysis reveals very few statistically significant differences in access to benefits between households when grouped on the basis of caste, followed by wellbeing ranks. However, political status and connectedness, namely membership in an executive committee, is significantly and positively associated with more lucrative benefits (e.g., timber, loan). Female-headed households are found always negatively (and significantly in some benefits) associated with all benefits. This study indicates that there is a need for a paradigm shift in studies and policies from caste- and wealth-based analysis to power, political status and connectedness to the decision-making bodies.
Keywords: 330; Access; Benefit sharing; Community forest; Dalit; Equity; Female headed households